Using a Hybrid ESG-BCG model to Guide Real Estate Strategy in Politically Fragile Markets: The Case of Palestine - Ghazal, Aqeed; Amro, Israa; Ramadan, Muawia; Global, Post-Catastrophe (Palestine Polytechnic University, 2025)
This study aims to develop a hybrid strategic frame work that integrates Environmental, Social, and Governance (ESG) principles with the Boston Consulting Group (BCG) Ma trix to support real estate investment decision-making in politi cally fragile markets. Using Jericho Gate Real Estate Company in Palestine as a case study, the research applies a qualitative, concept-driven methodology to assess the strategic positioning and sustainability performance of three key projects: the Com mercial Line, the proposed Indoor Amusement Park, and the Kid Mondo project. Each Project is initially classified using the tra ditional BCG Matrix, based on estimated market growth and rel ative project strength, followed by a layered ESG evaluation di mension -environmental impact, social, and governance readi ness. The analysis suggests that while the BGC Matrix remains useful in identifying investment priorities, it cannot capture non financial risks. The ESG layer compensates for this gap by high lighting critical factors that influence long-term stakeholder le gitimacy. The findings demonstrate that high-growth, high-ESG projects emerge as strategic priorities, whereas others may re quire phased planning, enhanced stakeholder engagement, and stronger governance frameworks. This integrated approach not only adds depth to strategic analysis but also highlights the grow ing importance of responsible, multidimensional planning in real estate, especially in regions shaped by uncertainty and limited in stitutional capacity.
Number of pages: 7, 2025 Engineering for Palestine Conference (ENG4PAL) PPU, Hebron, Palestine, September 29-30, 2025
Keywords: Hybrid ESG-BCG model, Guide, Real Estate Strategy, Politically Fragile Markets, Palestine